Evaluation of Ore Crushing and Grinding Performance For Lithium Recovery From Udawa Pegmatite Kaduna State - Isa, I.; Ajaka, E. O.; Adebayo, A. O.; Alabi, O. O. (Journal of Science, Technology and Innovation Research, 2025)
This study evaluates the crushing and grinding performance for lithium recovery from the Udawa pegmatite deposit in Kaduna State, Nigeria. The primary objective was to determine the optimal conditions for comminution to liberate lithium-bearing minerals. Ore characterization, including mineral liberation size, modal mineralogy and textural properties, was carried out using various laboratory techniques. Crushing was initially performed using the BICO Braun Chipmunk VD67 Jaw Crusher, followed by grinding in the SEPOR Ball Mill. The grindability and work index of the ore were determined to assess the ease of grinding and energy requirements for size reduction. Particle size analysis, using sieve analysis and SEM-EDX, revealed that an optimal mill speed of 15 RPM (300 revolutions) achieved the desired particle size of 1151 μm with 80% passing. The work index was calculated at 14.43 kWh/ton, indicating moderate energy consumption for grinding. The lithium content of the ore was found to peak at 3.63% in the -250 µm to +125 µm size range, suggesting that finer grinding would enhance lithium liberation. The study concludes that efficient grinding at 300 RPM is optimal for lithium recovery, and further exploration of beneficiation methods, including flotation and concentration, is recommended for maximizing recovery.